PENERAPAN MEDIA PAPAN PINTAR UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DAN SELF-EFFICACY SISWA KELAS III DI SD NEGERI TEGALMULYO - Insania Tyas Ningrum; Diyah Nur Arafah; Sofi Dian Rachmawati; Hermawan Wahyu Setiadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The difficulty of learning abstract mathematics often triggers anxiety and low self-efficacy in students, especially in inclusive classes that lack interactive media. This Classroom Action Research (CAR) aims to address these difficulties, improve conceptual understanding, and boost student self-efficacy through smartboard intervention. The research was conducted in the 2025/2026 academic year in third grade at Tegalmulyo Public Elementary School, Yogyakarta, with 25 students as subjects. Data were collected through testing, observation, interviews, and documentation. The results showed that the use of smartboards was effective as an interactive and flexible visual aid. This medium is able to present concrete material that stimulates active student engagement, facilitates conceptual understanding (such as object classification and mathematical representation), and enhances three aspects of student self-efficacy: level (optimism), strength (persistence), and generality (adaptability). It was concluded that the implementation of smartboards successfully created an inclusive, enjoyable, and effective mathematics learning environment, improving both cognitive performance and mental resilience in elementary school students.